PEDAGOGICAL CONDITIONS OF IMPROVEMENT VOCAL AND CHORAL SKILLS OF STUDENTS IN MUSIC LESSONS (Pedagogy of Higher and Secondary Education, 2003)
її is important for receiving positive results in a vocal-choral work to know and to create pedagogical conditions of rising of the quality of the vocalchoral work in the process o f pupils' education.Pedagogical conditions of form ing o f quality of vocal-choral work mean specially created conditions owing to which deep understanding of aesthetic content of a musical composition are carried out and its influence tothe personality strengthen.
Keywords: vocal-choral work; pedagogical conditions